SINTESIS SENYAWA KALSIUM FOSFAT DENGAN TEKNIK PRESIPITASI SINGLE DROP - I.P. Ramadani (Jurnal Biofisika, 2012)
The high damage of bone triggers a variety of research about bone biomaterial. So far, compliance for this needed done import materials. The material which used for bone biomaterial is calcium phosphate. In this research used synthesis of calcium phosphate. Synthesis of calcium phosphate performed using precipitation method single drop and wise drop at room temperature with sintering themperature 900 oC, themperature 70oC with sintering time variation (110oC, 300oC, 600oC, and 900oC). Results obtained from sintering are fluffy white powder. Result from x-ray diffraction characteristic for all sample with themperature sintering 900o C show the phase formed is calcium pyrophosphate and other phase from calcium phosphate that is hydroxyapatite, tricalcium phosphate, octacalcium phosphate, carbonate apatite type-A and carbonated apatite type-B. The longer stirring time is so the phase of calcium pyrophosphate formed the less. Reaction themperature is very effect in formation of phase calcium pyrophosphate, because calcium pyrophosphate which the resulting in room themperature is more than in themperature 70 oC. Beside that precursor compound that has not reacted in themperature 70oC less from room themperature, this is because precursor compound is faster when heated. In sintering variation themperature 110oC and 300oC the precursor formed is more and the best sintering themperature is 900oC.